2014
DOI: 10.5901/mjss.2014.v5n27p1458
|View full text |Cite
|
Sign up to set email alerts
|

School Community Participation and School Health Promotion: Challenges and Opportunities

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…According to the International Union for Health Promotion and Education (2009, cited by Clelland, Cushman & Hawkins 2013:1), the Health Promoting School (HPS) initiative maintains that, in order to successfully promote the long-term health and well-being of learners, schools must work closely with parents and the local community. In her research, Kwatubana (2014:1458) argues that ‘full, meaningful community participation completes any model of health promotion implemented in any schools’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the International Union for Health Promotion and Education (2009, cited by Clelland, Cushman & Hawkins 2013:1), the Health Promoting School (HPS) initiative maintains that, in order to successfully promote the long-term health and well-being of learners, schools must work closely with parents and the local community. In her research, Kwatubana (2014:1458) argues that ‘full, meaningful community participation completes any model of health promotion implemented in any schools’.…”
Section: Discussionmentioning
confidence: 99%
“…Community participation is referred to as both the processes and activities that allow members of a particular population to be heard, empowering them to be part of decision-making processes and enabling them to take action in conjunction with other structures on health promotion issues (Inter-Agency Network for Education in Emergencies 2004:80, cited by Kwatubana 2014:1458).…”
Section: Discussionmentioning
confidence: 99%
“…As regards community outreach, a Hong Kong study described that the schools under Healthy Schools Award scheme were more likely to be better school health policy, higher degrees of community participation, and better hygienic environment [ 63 ]. Community outreach in the schools’ activities is vital for the effectiveness of the HPS program and so, the school teachers should involve the school health activities closely with parents and the community [ 50 , 64 , 65 ]. In the benefits of the training and research activities, a qualitative study done in Bangladesh stated that the teachers’ training program related to school health had a positive impact on the ability, skills, and self-confidence of the teachers, who received training compared to the teachers who did not receive it [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have suggested the need for schools to understand school community participation, its importance, and execution [38,39]. School-based health promotion interventions can include the photovoice method for health education and can address various public health-related issues in school and community-based settings.…”
Section: Discussionmentioning
confidence: 99%